THU0607-HPR COMPARISON OF THE PATIENT REPORTED PHYSICAL ACTIVITY LEVEL ACCORDING TO KINESIOPHOBIA PRESENCE IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS. (13th June 2020) - Bayraktar, D.; Ozer Kaya, D.; Gucenmez, S.; Durak Ediboglu, E.; Kabadayi, G.; Akar, S.
Abstract : Background: Many factors such as poor functional or emotional status might play a role in participating physical activity for people with rheumatic diseases. There is a lack for evidence regarding to the effect of kinesiophobia presence on the physical activity levels of axSpA patients. Objectives: The primary objective was to compare the patient reported physical activity levels in axSpA patients with kinesiophobia and those without. Evaluating disease related and physical characteristics, quality of life and emotional status according to presence of kinesiophobia were also aimed. Methods: One-hundred forty-eight consecutive axSpA patient were allocated to Kinesiophobia+ group (n: 90, 66% males) or Kinesiophobia- group (n: 58, 64% males). The presence of kinesiophobia was defined as having a score of >37 in Tampa Scale for Kinesiophobia. All patients were evaluated regarding to physical characteristics (age, body-mass index), functional status (Bath Ankylosing Spondylitis Functional Index), disease activity (Bath Ankylosing Spondylitis Disease Activity Index), spinal mobility (Bath Ankylosing Spondylitis Metrology Index), patient reported physical activity (International Physical Activity Questionnaire Short Form), emotional status (Hospital Anxiety and Depression Scale), and quality of life (Assessment of SpondyloArthritis International Society Health Index). Results: Physical characteristics and spinal mobility were similar in patients with and without kinesiophobia (p>0.05, Table ). Disease activity, function, quality of life, depression and anxiety scores were poorer in Kinesiophobia+ group compared to Kinesiophobia- group (p<0.05, Table). Patient reported physical activity level was found to be lower in patients with kinesiophobia (p<0.05, Table). Conclusion: It seems that the presence of kinesiophobia may have a negative impact on patient reported physical activity level, and disease related parameters. However, it is also possible that kinesiophobia might occur as result of poor disease activity or disability. Strategies such as patient education should be included in axSpA management for preventing kinesiophobia development or improving kinesiophobia related consequences. Disclosure of Interests: None declared